Migrant women labor-force participation in Germany: Human capital, segmented labor market, and gender perspectives - Veronika J. Knize Estrada (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2018)
This paper analyzes individual, structural, and cultural factors that influence the labor-force participation of migrant women in Germany. Considering the well-established evidence that immigrant women work less than natives, with statuses and earnings differing significantly between them, I investigate the economic activity of the former by examining the cross-sectional data from the IAB-SOEP Migration Sample 2013 with multiple linear regression techniques. This evaluation is supported by three approaches which offer explanations for their employment behavior: human capital theory, segmented labor market theory, and the less examined in German research cultural hypothesis. Migrant women's employment status is, in principle, one's decision as member of a household; nevertheless, it is embedded in cross-national cultural processes and also constrained by structures; e.g., by employers and institutions. The analysis shows that classic human capital elements appear to be less reliable predictors of women's labor supply: higher education attained abroad is only marginally related to women participating in the workforce. The Middle-Eastern and North African origin, the Muslim religion, and higher levels of religiosity are negatively associated to women's labor participation reflecting a traditional gendered work division. This effect is minimized when controlling for German education, however. I argue that the lower labor-force participation among migrant women is partially explained by the fact that immigrants are on average less educated and more traditional than natives, having skills that are only restrictively transferable into the German labor market. – – Dieser Beitrag analysiert individuelle, strukturelle und kulturelle Faktoren, welche die Erwerbsbeteiligung von Migrantinnen in Deutschland beeinflussen. Migrantinnen weisen eine geringere Erwerbsbeteiligung als Einheimische auf und auch ihr Beschäftigungsstatus und ihre Verdienste unterscheiden sich stark. Deshalb untersuche ich die Erwerbsbeteiligung der Migrantinnen durch die Auswertung der Querschnittsdaten der IAB-SOEP Migrationsstichprobe 2013 mit einem multiplen linearen Regressionsansatz. Die Analyse stützt sich auf drei Ansätze, die Erklärungen für das Beschäftigungsverhalten von Migrantinnen bieten: die Humankapitaltheorie, die segmentierte Arbeitsmarkttheorie und die in der deutschen Forschung weniger untersuchte kulturelle Hypothese. Der Beschäftigungsstatus von Migrantinnen ist im Prinzip als die Entscheidung eines Haushaltsmitgliedes zu sehen, aber sie ist eingebettet in länderübergreifende kulturelle Prozesse und wird auch durch betriebliche bzw. institutionelle Strukturen eingeschränkt. Die Ergebnisse deuten darauf hin, dass klassische Elemente des Humankapitals weniger verlässliche Prädiktoren für das Arbeitskräfteangebot von Frauen sind: So wirkt sich eine im Ausland erworbene Hochschulbildung kaum auf die berufliche Teilhabe aus. Eine nahöstliche oder nordafrikanische Herkunft, die muslimische Religion sowie höhere Religiosität korrelieren mit der Erwerbsbeteiligung von Frauen negativ. Dies spiegelt eine traditionelle geschlechtsspezifische Arbeitsteilung wider, wobei eine Ausbildung in Deutschland diesen Effekt erheblich abschwächt. Die geringere Erwerbsbeteiligung von Migrantinnen dürfte damit teilweise dadurch erklärt werden, dass Zuwanderer im Durchschnitt weniger gebildet und traditioneller eingestellt sind als Einheimische. Zudem sind ihre Fähigkeiten nur beschränkt auf den deutschen Arbeitsmarkt übertragbar.
Keywords: O15; J15; J70; Z12; 330; female labor-force participation; migrant women; human capital theory; segmented labor market theory; gender attitudes; religion; cultural factors